Urinary corticoid to creatinine ratios using IMMULITE 2000 XPi for diagnosis of canine hypercortisolism - SAWAMURA, Hiryu; HOSOYA, Kenji; TAKIGUCHI, Mitsuyoshi; YOKOYAMA, Nozomu; NAKAMURA, Kensuke; SASAOKA, Kazuyoshi; SASAKI, Noboru; MORISHITA, Keitaro; NAGATA, Noriyuki; IKENAKA, Yoshinori (Journal of Veterinary Medical Science, 2022)
The urinary corticoid to creatinine ratio (UCCR) is one of the most commonly used screening tests for canine hypercortisolism (HC). In this study, a reference interval was established for UCCR using IMMULITE 2000 XPi, the latest chemiluminescence enzyme immunoassay. The diagnostic performance of this method for UCCR in canine HC was also evaluated. The median UCCR was 1.06 × 10−5 (range: 0.28–2.49) for 58 healthy dogs, and an upper reference limit of 1.98 × 10−5 (90% confidence interval: 1.76–2.15) was determined. The median UCCR in the 12 dogs with HC (7.38 × 10−5, range 1.86–29.98) was significantly higher than that in the 16 dogs with mimic-HC (1.59 × 10−5, range 0.47–3.42, P<0.001). The area under the curve for UCCR to differentiate HC dogs from mimic-HC dogs was 0.971, with a sensitivity of 91.7% and specificity of 100% when the cut-off value was set at 3.77 × 10−5. The UCCR of 16 paired urine samples collected at home and in hospital showed that the UCCR of samples collected in the hospital was significantly higher than that of samples collected at home (mean difference 3.30 × 10−5, 95% confidence interval: 0.70–5.90, P=0.001). In summary, we established the upper reference limit for UCCR using IMMULITE 2000 XPi in dogs and confirmed that UCCR is a useful diagnostic test for HC in dogs if urine samples are collected at home.